Translanguaging perspectives on writing development and pedagogy : learning from findings across teaching and learning contexts - Gort, Mileidis; Zapata, Angie; Seltzer, Kate; Gómez, Margarita (Emerald Publishing Limited, 2025)
Translanguaging Perspectives on Writing Development and Pedagogy takes up translanguaging perspectives on writing development and writing pedagogies across a variety of contexts. The chapters explore how a translanguaging lens - which is rooted in the idea that bi/multilingual people draw from an integrated repertoire of language features, rather than use separate, named languages, to communicate and make meaning - can shift and expand notions of writing practices and instruction. Individual chapters illustrate rich, descriptive studies of writing across three contexts: K-12 classrooms and schools, learning environments that extend beyond the classroom, and pre- and in-service teacher education, framing the book's three-part organization. Highlighting meaningful collaborations with teachers, students, families, and community members, the volume offers innovative methodologies and approaches to research relationships in language- and literacy-learning spaces. Translanguaging Perspectives on Writing Development and Pedagogy advances a comprehensive view of translanguaging perspectives on writing and how such a perspective can shift traditional approaches to the research on and teaching of writing.
Includes index.
Keywords: Translanguaging (Linguistics); Education -- Bilingual Education.; Teaching skills and techniques.; Education of bilingual or multilingual students.; elektronické knihy; electronic books